Enriching strategic variety in new ventures through external knowledge - Larrañeta, Bárbara; Zahra, Shaker A.; González, José Luis Galán (Journal of Business Venturing, 2012)
To build profitable market positions, new ventures have to address multiple challenges on several fronts. These ventures can compete by being simple (focused) or applying varied ways to compete. The likelihood of these ventures remaining competitive depends on their ability to build novelty into their products and operations, an activity that requires infusing knowledge into their operations. Most ventures, however, have limited knowledge bases and the reach (scope) of their external connections is limited, a factor that prompts them to tap into different external sources in their local areas. This article reports an empirical study of 140 new ventures located in seven regional clusters in Spain. The results show that new ventures can enrich the variety of their strategic repertoire by accessing diverse sources of external knowledge and being exposed to external novel knowledge, while absorptive capacity moderates this relationship. The degree of social development of these clusters also has a positive impact on the strategic variety of new ventures, exhibiting an inverted U-shape curve.